Developing English Vocabulary Through Riddle Cards: A Study At Mts. Darul Karomah - Siti Holilah; Yahmun; Endang Sumarti (Universitas Insan Budi Utomo, 2025)
The purpose of this study is to develop riddle cards as a medium for English vocabulary instruction at MTs. Darul Karomah. This study is grounded in the concept of 'Developing Riddle Cards as a Medium for English Vocabulary Instruction' and focuses on the development of printed learning media. The research was conducted using a questionnaire distributed to material experts, media experts, teachers, and students to provide feedback on the product. The findings indicate that the developed riddle cards are more effective in promoting English vocabulary acquisition among English language learners compared to traditional learning media. Additionally, this study aims to provide a reference for the use of riddle cards as a learning medium for English vocabulary and assist students in English language learning.